PENGARUH LINGKUNGAN KERJA, KAPABILITAS DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PT. JASA RAHARJA CABANG UTAMA JAWA TENGAH - Rahmaningtyas, Aulia; Syaflan, Meidi (Jurnal Riset Mahasiswa, 2024)
The design of this study is a quantitative study, namely research that explains the causal relationship between variables through hypothesis testing (Sekaran, 2006:45). This research was conducted to determine the effect of work environment, capability and compensation on the performance of employees of PT. Jasa Raharja Main Branch of Central Java, using the multiple regression formula, t test, F test and R test to 61 people who were the samples in this study. The results of this study are (1) There is a positive influence on the performance of employees of PT Jasa Raharja Main Branch of Central Java, with a coefficient of 0.400. From the t test, it is found that t count = 3,520 > t table = 1,672, then Ho is rejected and Ha is accepted; (2) There is a positive influence on the performance of employees of PT Jasa Raharja Main Branch of Central Java, with a coefficient of 0.312. From the t-test, it is found that t count = 4.043 > ttable = -1.672 then Ho is rejected and Ha is accepted; (3) There is a positive influence on the performance of employees of PT. Jasa Raharja Main Branch of Central Java, with a coefficient of 0.303. From the t test, it is found that t count = 2,569 > t table = 1,672, then Ho is rejected and Ha is accepted; (4) From the above test, it is obtained that f count = 370.985 > f table = 2.766 then H0 is rejected and Ha is accepted, so it can be concluded that there is a simultaneous significant effect on the variables of Work Environment (X1), Capability (X2), Compensation ( X3), on the performance of employees of PT Jasa Raharja Main Branch of Central Java (Y).